Experimental model for controlled endoscopic subepithelial vocal fold injury in rats - Ujvary,Laszlo Peter (2022)
ABSTRACT Purpose: To present a detailed, reproducible, cost-efficient surgical model for controlled subepithelial endoscopic vocal fold injury in the rat model. Methods: Six male Sprague Dawley rats were enrolled in the experiment. The left vocal folds were used to carry out the injury model, and the right vocal fold served as control. After deep sedation, the rats were placed on a custom operating platform. The vocal fold injury by subepithelial stripping was carried out using custom-made microsurgical instruments under endoscopic guidance. Data were analyzed for procedural time and post-procedural pain. Microcomputed tomography (micro-CT) scan and histologic images were obtained to assess the length, area, and depth of injury to the vocal fold. Results: The mean procedural time was 112 s. The mean control vocal fold length was 0.96 ± 0.04 mm. The mean vocal fold injury length was 0.53 ± 0.04 mm. The mean vocal fold surface was 0.18 ± 0.01 mm2 with a mean lesion area of 0.05 ± 0.00 mm2. Mean vocal fold injury depth was 375.4 ± 42.8 μm. The lesion length to vocal fold length ratio was 0.55 ± 0.03, as well as lesion area to vocal fold surface area was 0.29 ± 0.02. Conclusions: Our described experimental vocal fold injury model in rats is found to be fast, safe, cost-efficient, and reproducible with a rapid learning curve.